Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.4149/neo_2009_05_379
|View full text |Cite
|
Sign up to set email alerts
|

Reduced inducibility of SOCS3 by interferon gamma associates with higher resistance of human breast cancer lines as compared to normal mammary epithelial cells

Abstract: The resistance to interferons (IFNs) limits their anticancer therapeutic efficacy. Here we studied the antiproliferative effect of interferon gamma in relation to SOCS3 expression in a panel of breast cancer cell lines and normal mammary epithelial cells. Compared to normal cells most breast cancer lines (7/8) were highly resistant to IFN-gamma. Using Northern blot and real time RT-PCR we investigated transcription of SOCS3 genes. All normal epithelial cells (4/4) showed SOCS3 induction (2-14 fold) while most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…In normal breast epithelial cells SOCS3 is induced, while in several breast cancer cell lines SOCS3 is weakly activated. In breast tumour cells, it has been postulated that the IFNγ induced anti-proliferative effects are reduced due to a lower sensitivity to SOCS3 induction [19]. Our in vitro studies identified that IL11 (from 1 ng/ml) stimulated SOCS3 protein abundance in non-carcinoma HES cells.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In normal breast epithelial cells SOCS3 is induced, while in several breast cancer cell lines SOCS3 is weakly activated. In breast tumour cells, it has been postulated that the IFNγ induced anti-proliferative effects are reduced due to a lower sensitivity to SOCS3 induction [19]. Our in vitro studies identified that IL11 (from 1 ng/ml) stimulated SOCS3 protein abundance in non-carcinoma HES cells.…”
Section: Discussionmentioning
confidence: 54%
“…In addition critical roles for pSTAT3 and SOCS3 in cancer have also been proposed [8,18,19]. Tumor cell survival depends on the cells' ability to adhere to, migrate and invade through the tissue and to metastasize into other organs and tissues [20].…”
Section: Introductionmentioning
confidence: 99%
“…Human IFNγ‐secreting MDA‐MB‐231 tumour cell lines (MDA‐hIFNγ) were constructed, with MDA‐m cells as a control. MDA‐MB‐231 cells were IFNγ‐resistant ; thus, the action of local hIFNγ on HUVECs could be analysed in vivo . MDA‐hIFNγ (or MDA‐m) with HUVEC‐Dll4 (or HUVEC‐m) cells were co‐injected into SCID mice, with MDA‐m as a control.…”
Section: Resultsmentioning
confidence: 99%